Measuring the Relationship between Perceived Quality and Satisfaction in Restaurants: A Case Study in a Chinese Buffet Restaurant - YUN, DI (2009)
This study examines which factors of the Chinese buffet restaurant (hereinafter CBR) influence customer satisfaction, using multiple-regression analysis approach and Structural Equation Modeling (SEM). The multiple-regression analysis indicates that food is the most significant influential factor on customer satisfaction, followed by price factor, ambience factor, and service factor orderly. Among them, ambience quality provided maybe the weakness area where the CBR need to improve. In addition, no moderating variables are found in this study. SEM supports multiple-regression analysis results with respect to the influencing power of food factor and ambience factor on customer satisfaction. However, it shows that service factor is not significant for customer satisfaction, and it cannot get better explanations if price factor involved. Accordingly, the CBR’s manager should allocate limited resources to restaurant quality factors based on their contributions to customer satisfaction, in order to maximize customer satisfaction efficiently and effectively.